Transfer of Finnish adolescents with epilepsy to adult care: a population-based study - Sillanpää, Matti L.; Reinhold, Vivian; Toivonen, Leevi; Camfield, Peter R. (Elsevier BV, 2026)
Background
Transferring adolescents with epilepsy (AWE) to adult care is a complex process, yet there is limited data on its overall epidemiology and clinical implications.
Objective
This population-based study analyzes the long-term clinical trajectories and predictors of transfer among AWE within a robust Finnish healthcare system.
Methods
A cohort of 439 AWE was followed for a mean of 10.28 years. Transfer outcomes, care settings, and long-term seizure control were evaluated for patients reaching transfer age, focusing on predictors of public adult specialty care.
Results
Of 222 AWE reaching transfer age, 189 (85.1 %) were transferred to adult services, with 64 % entering university hospital care. Remission was achieved in 23 % during extended follow-up, while 27 % remained drug-resistant. Multivariable analysis identified developmental and epileptic encephalopathy, specific developmental disorders, and comorbidities such as asthma, allergies, and obesity as significant predictors for public adult specialty care. Notably, changing the transfer age from 16 to 18 years had no significant effect on transfer rates.
Conclusion
Transfer to adult specialty care affects the vast majority of AWE, imposing considerable demands on public health systems. These findings underscore the need for early identification of high-risk patients to inform resource planning and individualized care strategies.